2014
DOI: 10.1371/journal.pone.0089269
|View full text |Cite
|
Sign up to set email alerts
|

Plaque Bacterial Microbiome Diversity in Children Younger than 30 Months with or without Caries Prior to Eruption of Second Primary Molars

Abstract: ObjectiveOur primary objective is to phylogenetically characterize the supragingival plaque bacterial microbiome of children prior to eruption of second primary molars by pyrosequencing method for studying etiology of early childhood caries.MethodsSupragingival plaque samples were collected from 10 caries children and 9 caries-free children. Plaque DNA was extracted, used to generate DNA amplicons of the V1–V3 hypervariable region of the bacterial 16S rRNA gene, and subjected to 454-pyrosequencing.ResultsOn av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
99
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 46 publications
18
99
1
3
Order By: Relevance
“…clone, PCR, HOMIM[44]M/F 55 (±53.8–56.3) Leptotrichia sp. clonesHealthy and diseases (caries + periodontitis)Saliva, mouth A. xylosoxidan , M. micronuciformis , F. periodontium , V. atypica , PCR, HOMIM 124M/F < 30 Mo ±19.1 Leptotrichia spp., L. hongkongensis clonesCariesSupragingival plaque, mouth Porphyromonas , Corynebacterium, Capnocytophaga , Streptococcus spp., S. mutans clones, S. sobrinus clones, Veillonella, Neisseria , Rothia , TM7 genus incertae sedis , Actinomyces, Prevotella spp., P. histicola clones, Eikenella, Kingella , Fusobacterium, Gemella , Campylobacter, Granulicatella spp., G. adiacens clones, Abiotrophia, Selenomonas , Acinetobacter, Lactobacillus , Anaeroglobus, Ottowia , Schlegelella , HTS, PCA[45]M/F < 30 Mo ±19.0 Leptotrichia spp.CFSupragingival plaque, mouth Streptococcus spp., Capnocytophaga, Corynebacterium , TM7 genus incertae sedis , Porphyromonas, Granulicatella , Fusobacterium, Treponema , Gemella, Selenomonas , Veillonella, Dechloromonas , Actinomyces, Campylobacter , Abiotrophia , Ottowia , Eikenella, Johnsonella , Neisseria, Prevotella , Kingella, Rothia , HTS, PCA 126M/F/T 39 ± 10 Leptotrichia spp.HIV seropositiveSaliva Lactobacillus spp., Aggregatibacter, Lachnospiraceae , Rothia, Eubacterium , Tannerella, Haemophilus , Neisseria, Gemella , Granulicatella, Shuttleworthia , Streptococcus, S. mutans , Fusobacterium, Solobacterium , Campylobacter, Veillonella , Dialister , Synergistetes, Filifactor, Parvimonas , Achromobacter , Megasphaera, Selenomonas, Prevotella , Candida , culture, DGGE, HOMIM, PCA[46]M/F 43 ± 13 Leptotrichia spp.HIV seronegativeSaliva Capnocytophaga , Lachnospiraceae, Peptostreptococcaceae , Granulicatella, Veillonella , Synergistetes, Lactobacillus spp., Porphyromonas, Lactobacillus , Campylobacter, Streptococcus , S. mutans , Parvimonas, Kingella , Atopobium, Selenomonas , Aggregatibacter, Fusobacterium , Haemophilus, Megasphaera , Prevotella, Solobacterium , Gemella, Achromobacter , Eubacterium, Rothia , Slackia, Filifactor , Dialister, Neisseria , Candida , culture, DGGE, HOMIM, PCA 128M/F ≥ 18–21.5 ± 1.9 Leptotrichia spp., L. hongkongensis Healthy, supragingival plaqueMouth Corynebacterium , Capnocytophaga, Streptococcus , Cardiobacterium , Hae...…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…clone, PCR, HOMIM[44]M/F 55 (±53.8–56.3) Leptotrichia sp. clonesHealthy and diseases (caries + periodontitis)Saliva, mouth A. xylosoxidan , M. micronuciformis , F. periodontium , V. atypica , PCR, HOMIM 124M/F < 30 Mo ±19.1 Leptotrichia spp., L. hongkongensis clonesCariesSupragingival plaque, mouth Porphyromonas , Corynebacterium, Capnocytophaga , Streptococcus spp., S. mutans clones, S. sobrinus clones, Veillonella, Neisseria , Rothia , TM7 genus incertae sedis , Actinomyces, Prevotella spp., P. histicola clones, Eikenella, Kingella , Fusobacterium, Gemella , Campylobacter, Granulicatella spp., G. adiacens clones, Abiotrophia, Selenomonas , Acinetobacter, Lactobacillus , Anaeroglobus, Ottowia , Schlegelella , HTS, PCA[45]M/F < 30 Mo ±19.0 Leptotrichia spp.CFSupragingival plaque, mouth Streptococcus spp., Capnocytophaga, Corynebacterium , TM7 genus incertae sedis , Porphyromonas, Granulicatella , Fusobacterium, Treponema , Gemella, Selenomonas , Veillonella, Dechloromonas , Actinomyces, Campylobacter , Abiotrophia , Ottowia , Eikenella, Johnsonella , Neisseria, Prevotella , Kingella, Rothia , HTS, PCA 126M/F/T 39 ± 10 Leptotrichia spp.HIV seropositiveSaliva Lactobacillus spp., Aggregatibacter, Lachnospiraceae , Rothia, Eubacterium , Tannerella, Haemophilus , Neisseria, Gemella , Granulicatella, Shuttleworthia , Streptococcus, S. mutans , Fusobacterium, Solobacterium , Campylobacter, Veillonella , Dialister , Synergistetes, Filifactor, Parvimonas , Achromobacter , Megasphaera, Selenomonas, Prevotella , Candida , culture, DGGE, HOMIM, PCA[46]M/F 43 ± 13 Leptotrichia spp.HIV seronegativeSaliva Capnocytophaga , Lachnospiraceae, Peptostreptococcaceae , Granulicatella, Veillonella , Synergistetes, Lactobacillus spp., Porphyromonas, Lactobacillus , Campylobacter, Streptococcus , S. mutans , Parvimonas, Kingella , Atopobium, Selenomonas , Aggregatibacter, Fusobacterium , Haemophilus, Megasphaera , Prevotella, Solobacterium , Gemella, Achromobacter , Eubacterium, Rothia , Slackia, Filifactor , Dialister, Neisseria , Candida , culture, DGGE, HOMIM, PCA 128M/F ≥ 18–21.5 ± 1.9 Leptotrichia spp., L. hongkongensis Healthy, supragingival plaqueMouth Corynebacterium , Capnocytophaga, Streptococcus , Cardiobacterium , Hae...…”
Section: Figurementioning
confidence: 99%
“…Since previous reviews [2,3], Leptotrichia species have been reported in >124 cases [4,7,16,1869,8793], whereby 30 cases involved L. buccalis [4,8,15,21,34,52,56,70–79,87], 24 cases L. wadei [4,20,24,34,37,42,48,56,67,80,81,90,93], 16 cases L. trevisanii [4,5,9,10,13,14,17,37,87], 14 cases L. hofstadii [34,40,49,56,8184,93], 10 cases L. goodfellowii [4,11,12,21,56,74,85,87], eight cases L. hongkongensis [4,6,18,45,47,56], and five L. shahii [34,56,86]. L. trevisanii and L. wadei bacteremia are extremely rare; clinicians should consider these species in cases involving immunocompromised patients with oral lesions [4,5,13,17,87].…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…tween 7 and 36 months, and all studies linked MS detection to the time period coinciding with eruption of the primary teeth [Carlsson et al, 1975;Alaluusua and Renkonen, 1983;Fujiwara et al, 1991;Xu et al, 2014].…”
mentioning
confidence: 99%